A First Version of the Caenorhabditis elegans Promoterome - Dupuy, Denis; Li, Qian-Ru; Deplancke, Bart; Boxem, Mike; Hao, Tong; Lamesch, Philippe; Sequerra, Reynaldo; Bosak, Stephanie; Doucette-Stamm, Lynn; Hope, Ian A.; Hill, David E.; Walhout, Albertha J.M.; et al. (Genome Research, 2004)
An important aspect of the development of systems biology approaches in metazoans is the characterization of expression patterns of nearly all genes predicted from genome sequences. Such “localizome” maps should provide information on where (in what cells or tissues) and when (at what stage of development or under what conditions) genes are expressed. They should also indicate in what cellular compartments the corresponding proteins are localized. Caenorhabditis elegans is particularly suited for the development of a localizome map since all its 959 adult somatic cells can be visualized by microscopy, and its cell lineage has been completely described. Here we address one of the challenges of C. elegans localizome mapping projects: that of obtaining a genome-wide resource of C. elegans promoters needed to generate transgenic animals expressing localization markers such as the green fluorescent protein (GFP). To ensure high flexibility for future uses, we utilized the newly developed MultiSite Gateway system. We generated and validated “version 1.1” of the Promoterome: a resource of ∼6000 C. elegans promoters. These promoters can be transferred easily into various Gateway Destination vectors to drive expression of markers such as GFP, alone (promoter::GFP constructs), or in fusion with protein-encoding open reading frames available in ORFeome resources (promoter::ORF::GFP).